Reconstruction of the Implementation of Child Rights Protection Regulations Post-Divorce in Law Enforcement Practices in Religious Courts - Yudawati, Nila; Widayati, Widayati (UNISSULA Semarang, 2025)
This research is motivated by the implementation of post-divorce child protection regulations in law enforcement practices in Religious Courts which have not been effective. This can be seen in a number of divorce case decisions in Religious Courts, especially those decided without the presence of the parties (verstek or in absentia), have not guaranteed the fulfillment of children's rights compared to granting the main case of the divorce suit itself. While child protection is part of the implementation of Human Rights and is a mandate of the 1945 Constitution of the Republic of Indonesia Article 27 paragraph (1) and Article 28B paragraph (2), in the implementation of post-divorce child protection regulations until now there are still various problems that arise both in terms of Human Resources, legal umbrella, facilities and infrastructure and the active role of society and government. In terms of Human Resources related to the activeness of judges in making decisions related to children's rights, in terms of the legal umbrella, existing child protection regulations also still need to be revised because there are still things that need to be regulated, in terms of facilities and infrastructure, it is also necessary to improve the database and compatible IT-based applications, and in terms of socio-cultural, the role of society and government in implementing post-divorce child rights protection is still weak. This research is qualitative, using descriptive methods and supported by a juridical-normative and juridical-sociological approach. Data collection sources and techniques are obtained from primary and secondary data sources related to the research object. Data analysis techniques use a deductive approach until research conclusions are formulated. The results of this study indicate that the implementation of regulations on the protection of children's rights after divorce in law enforcement practices in Religious Courts has not been fully implemented even though there are various positive laws that regulate it, there are various obstacles and require concrete solutions to problems that hinder the implementation of these children's rights. The main obstacle to the implementation of regulations on the protection of children's rights in Religious Courts is the lack of breakthroughs by judges in making new legal discoveries and also harmonization of protection regulations related to the protection of children's rights. While the solution is to harmonize the regulations that serve as the legal umbrella for the protection of children's rights after divorce and change the judge's paradigm regarding the provision of decisions that favor children's rights after divorce to enforce the implementation of children's rights after divorce in Religious Courts, reconstruction is needed. carried out by way of legal reform through three ways, namely: constitutional approach; structural approach; and cultural approach. In addition, government and non-government institutions also play an active role in providing protection for children's rights in Indonesia.